2023
DOI: 10.3390/foods12142772
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Microstructural and Rheological Properties of Frozen Unfermented Wheat Dough with Laccase and Ferulic Acid

Ni He,
Zhiqin Pan,
Lin Li
et al.

Abstract: The quality deterioration that is induced by freezing treatment limits the development of frozen dough technology for standardized and delayed baking. In this study, laccase (LAC) and ferulic acid (FA) were employed to improve the rheological properties and microstructure of frozen unfermented dough. The results showed that the dough with LAC + FA had a lower softening degree than the dough with FA alone. Correspondingly, LAC + FA incorporation enhanced the viscoelastic behavior of frozen unfermented dough wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…During storage with temperature fluctuation, dough-based foods may suffer serious quality problems due to ice crystal growth and recrystallization. It was found that frozen dough loses water after freezing and thawing and that large ice crystals in the dough destroy the internal structure, leading to the separation of starch granules and the protein network structure [7]. Moreover, the water distribution and microstructure of frozen dough can be altered by multiple freeze-thaw cycles, for example, promoting ice recrystallization, disrupting the interaction between dough components and water molecules, and depolymerizing the high-molecular-weight portion of gluten [8].…”
Section: Introductionmentioning
confidence: 99%
“…During storage with temperature fluctuation, dough-based foods may suffer serious quality problems due to ice crystal growth and recrystallization. It was found that frozen dough loses water after freezing and thawing and that large ice crystals in the dough destroy the internal structure, leading to the separation of starch granules and the protein network structure [7]. Moreover, the water distribution and microstructure of frozen dough can be altered by multiple freeze-thaw cycles, for example, promoting ice recrystallization, disrupting the interaction between dough components and water molecules, and depolymerizing the high-molecular-weight portion of gluten [8].…”
Section: Introductionmentioning
confidence: 99%